The Virtual World’s Current Addiction: Phubbing - Karadağ, Engin; Tosuntaş, Şule Betül; Erzen, Evren; Duru, Pınar; Bostan, Nalan; Şahin, Berrak Mızrak; Çulha, İlkay and Babadağ, Burcu (Addicta: The Turkish Journal on Addictions, 2016)
The aim of this work is to analyze both the reasons that young adults exhibit phubbing behaviors and the effects of these behaviors on their lives. Following a qualitative research approach, this study has been designed using a case study method. Selected using the criterion sampling method, participants consisted of a total of 9 university students studying in a School of Education in Turkey. The criterion used to include individuals into the sample group was ‘using a smartphone instead of actively participating in an on-going discussion being had by one’s surrounding peers’ as well as a high score on the Phubbing Scale form. Data were obtained using a semi-structured interview form composed of 18 open-ended questions. Both a descriptive and content analysis were used to evaluate the data. The study’s findings revealed that not only did smartphones negatively affect interpersonal relations, but also that phubbers lacked communication skills, experienced difficulty establishing and maintaining eye contact while using a smartphone, and misunderstood what was being discussed. Some participants even stated that they would become completely disconnected from the social environment while using a smartphone. It is argued in the discussion section that since smartphones have all the same features and abilities as traditional computers, they carry the same potential addictions as computers. Yet, instead of being restricted to a table, these addictions are now able to manifest in every aspect, environment, and moment of one’s life. As such, since phubbing carries with it a type of addiction that is much more devious and pervasion than most previous virtual reality related addictions, it is recommended that further research be conducted before serious psychopathological and sociological problems begin to manifest themselves throughout the population. Citation: Karadağ, E., Tosuntaş, Ş. B., Erzen, E., Duru, P., Bostan, N., Mızrak Şahin, B., ... Babadağ, B. (2016). The virtual world’s current addiction: Phubbing. Addicta: The Turkish Journal on Addiction, 3, 250–269. http://dx.doi.org/10.15805/ addicta.2016.3.0013